The European Union's strategy for Africa – coherence in the face of a complex, changing continent? - Sven Grimm; Nina Kielwein (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
In October 2005 the European Commission proposed a Strategy for Africa to be pursued by the European Union (EU). The European Council will decide on the strategy in December. What is new about this strategies and policies of the Commission, Member States and European Community within a single framework. The main aim of the strategy is to foster the achievement of the Millennium Development Goals (MDGs) in Africa. Security, good governance and the economic environment are seen as preconditions for their lasting achievement. As entry points for cooperation the Commission identifies in its draft African reforms under the New Partnership for Africa (NEPAD). The strategy is thus an attempt to react to recent continental developments in Africa, avoiding any temptation to take an indiscriminate view of the continent and emphasizing a country-specific approach. The strategy's great merit may lie in the resolution of conflicts of objectives at the policy-making level and the reduction of coordination conflicts within the EU. It is, then, primarily an attempt to attain greater coherence in the policy of the whole EU towards Africa. It therefore provides reference points to all the various actors in European foreign relations, but it cannot eliminate the critical institutional weaknesses, which include, for example, the fragmentation of authority within the Commission. The implementation of the strategy will largely depend on the Member States. The main challenges will be to put in to effect the collective EU target of a progressive de facto doubling of Official Development Aid (ODA) by 2015. Internal coherence of all European actors, the complementarity of the Member States' and Commission's policies and closer on-the-spot coordination must also be seen as critical issues. During its presidency of the EU Council in the first half of 2007 Germany may face the task of making the implementation of the Strategy for Africa into an important topic.
Keywords: 330